Unfolding Democratic Process in Jammu and Kashmir in Post 2019- Period: A Study of DDC Elections - Nisa, Jameelun (Indian Journal of Political Science)
The paper traces the nature of democratic politics, particularly the party politics after the state of Jammu and Kashmir was reorganized as Union territory. It specifically focus on Kashmir- based political parties, particularly the National Conference and Peoples Democratic Party, as well as other parties including the newly floated Apni Party and the Peoples Conference. The paper argues that the parties like PDP and NC have been facing crisis in the post- reorganisation phase for a number of reason. First, these parties have lost their ideological ground based on Article 370. With abrogation of the special constitutional status of the state, these two parties have lost major agenda of their party because NC was mainly promising ' Autonomy' and the PDP was promising 'Self Rule'. This is no more possible with Article 370 being amended. Also these parties have been losing their cadre to other parties for Instance, the PDP has lost all the senior leader either to Apni Party or to the People Conference. Though National Conference has not faced crisis to that extent but even this party has lost senior leaders not only to Apni party and peoples Conference but also a Bhartiya Janta Party. The paper focuses on the democratic space in post-2019 period, particularly in the District Development Council Election and the performance of various parties in it. The paper also refer to the All Party Meeting which was addressed by the Prime Minister in 2021. - Reproduced
Keywords: PDP, NC, BJP, Party Politics, Autonomy, Self- Rule